Changes in the Structure of Earnings During the Polish Transition - Michael P. Keane; Eswar S. Prasad (Institute for the Study of Labor (IZA), 2002)
We document changes in the structure of earnings during the economic transition in Poland. We find that inequality in labor earnings increased substantially from 1988 to 1996. A common view is that the reallocation of workers from a public sector with a compressed wage distribution, to a private sector with much higher wage inequality, accounts for the bulk of increased earnings inequality during transition. However, our decomposition of the sources of the increase in inequality suggests that this compositional effect accounts for only 39% of the increase. Fully 52% of the increase is due to the increase in the variance of wages within sectors. That is, earnings inequality within both the private and public sectors grew substantially, and by similar amounts. This illustrates how even state-owned enterprises in Poland moved towards competitive wage setting as they restructured. A substantial part of the increase in earnings inequality was between group, due largely to increased education premia. However, changes in inequality within education-experiencegender groups account for about 60 percent of the increase in overall wage inequality–similar to the patterns observed in the U.S. and U.K. in the 1980s. But, in contrast to the U.S. and U.K. experiences, increases in within-group inequality in Poland were very different across skill groups, with much larger increases for highly educated workers. These patterns hold in both the private and public sectors, although increases in education premia were somewhat greater in the private sector.
Keywords: J31; O33; P20; 330; wage inequality; between and within-group inequality; education and experience premia; labor reallocation; transition; Lohnstruktur; Einkommensverteilung; Übergangswirtschaft; Strukturwandel; Humankapital; Schätzung; Polen